Prevalence of stress and anxiety among parents of COVID-19 positive children admitted in Kempegowda hospital, Bengaluru - Ramya, H. S.; ., Keerthidarshini; Asiya, Afroza; L., Sanjay (International Journal of Contemporary Pediatrics, 2021)
Background: COVID-19 pandemic has led to rise in fear, anxiety, stress among population. Parents of COVID-19 positive children are most vulnerable of all, since they have to bear the economic burden and the fact that there is no definitive treatment which might end up with fear of uncertainty of bad outcome added to their stress. The aim of the study was to assess the level of stress and anxiety among parents of COVID-19 positive children admitted in Kempegowda hospital, Bangalore. Methods: Cross-sectional study was done in Kempegowda hospital. Total of 50 COVID-19 positive children were admitted in Kempegowda Hospital. 23 were boys and 27 were girls. Parents were explained about the DASS-21 questionnaire to assess stress and anxiety and relevant options were marked by the paediatrics post graduate posted in the COVID-19 ward. Association of mental health disorders such as stress and anxiety with symptoms, contact history, nutritional status and other demographic factors were analyzed using Chi square test. Results: Female to male ratio was 1.1:1. Among the 50 children, 80% had contact history with COVID-19 positive individuals. 24 (48%) were symptomatic, among which 7 individuals had fever, 7 individuals had cough, 3 individuals had cold, 2 children had respiratory distress and remaining had myalgia (2), loose stools (2) and pain abdomen (1). 82% parents had stress and 60% had anxiety. Conclusions: Severe stress and moderate anxiety levels was majorly seen in parents of symptomatic COVID-19 positive children during the hospital stay suggesting the need for counselling of parents and awareness of impact of COVID-19 infection in children.